2020
DOI: 10.3390/su12124872
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Support and Adaptive Performance: The Revolving Structural Relationships between Job Crafting, Work Engagement, and Adaptive Performance

Abstract: This study has two primary purposes: (1) examining the structural relationships between organizational support, job crafting, work engagement, and adaptive performance, and (2) identifying a revolving relationship derived from these relationships. To that end, the research sampled 250 human resources professionals in companies with at least 300 employees in South Korea and employed structural equation modeling. The study’s findings showed that organizational support affects adaptive performance through job cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 47 publications
11
35
0
3
Order By: Relevance
“…In line with these studies, the findings of our research indicate that perception of organizational support leads to favorable outcomes (i.e., employee flourishing). Our study findings were also consistent with POS and work engagement linkage literature that there is positive relationship [71][72][73]. Our study also showed that POS is the major contributor to employee work engagement by validating this finding in the Asian context.…”
Section: Discussionsupporting
confidence: 91%
“…In line with these studies, the findings of our research indicate that perception of organizational support leads to favorable outcomes (i.e., employee flourishing). Our study findings were also consistent with POS and work engagement linkage literature that there is positive relationship [71][72][73]. Our study also showed that POS is the major contributor to employee work engagement by validating this finding in the Asian context.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, POS is considered as one of the factors influencing job crafting because POS encourages employees to be more creative, obtain more resources and change the meaning of their work (Saragih.S et al, 2020). This expression is in line with research by Mallick (2018), and Park et al (2020) which explains if there is a positive influence between perceived organizational support on job crafting. However, it is inversely proportional to the research of Saragih.S et al, (2020) which states that there is no statistically significant relationship between POS and Job crafting.…”
Section: Introductionsupporting
confidence: 91%
“…Job crafting itself is an attitude that can inspire employees to be more dedicated to their work with high attention and energy (Park et al, 2020). This can be interpreted that job crafting has an influence on work engagement (Park et al, 2020). This statement is supported by research from Ogbuanya & Chukwuedo (2017), Monita (2020), Albana (2018), and Syah (2020) where job crafting has a significant positive effect on work engagement.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, a person who share similar values may give better performance because they can predict coworker's behavior (Amarneh, & Muthuveloo, 2020). Additionally, research denotes that PG fit has positive correlation with Adaptive Performance (Park, Lim, Kim, & Kang, 2020) as well as with adaptive performance because it is also under Adaptive Performance domain. Thus, based on the past literature, following hypothesis has been developed.…”
Section: Literature Review Person-group (Pg) Fit and Adaptive Performance (Ap)mentioning
confidence: 96%